2004
DOI: 10.1001/archfaci.6.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for Masseter Reduction in Asian Patients

Abstract: sian patients frequently seek aesthetic alteration of hypertrophic masseter muscles to reduce a prominent mandibular angle. Surgical reduction is common in Asia, but botulinum toxin offers a less invasive approach. This pilot study evaluated results of aesthetic lower face narrowing in 20 Asian patients. Initially, 25 U of botulinum toxin (5 U/0.1 mL) was injected at each inferior masseter border; an additional 25 U was injected per side as needed at 1-week intervals. Seven patients (35%) required only 1 injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…An oval facial shape with a smooth flow from the forehead through temples, zygoma and cheeks, jaw angle and jawline, and the chin has been reported to be attractive in all cultures [4, 10, 11]. Ahn et al [12] reported that a delicate ovoid facial shape is favoured in Asia. Similarly, Park et al reported that “oval and almond-shape faces” are preferred by Asian women [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An oval facial shape with a smooth flow from the forehead through temples, zygoma and cheeks, jaw angle and jawline, and the chin has been reported to be attractive in all cultures [4, 10, 11]. Ahn et al [12] reported that a delicate ovoid facial shape is favoured in Asia. Similarly, Park et al reported that “oval and almond-shape faces” are preferred by Asian women [13].…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular angle is an example of this belief and plays a very important role in female facial shape in Asia: “a woman who has a wide and square face is thought to have had a unhappy life” [21]. Accordingly, surgical and non-surgical reduction in the lower face width is a common request and a very popular practice in Asia [12, 15, 22, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…hypertrophy is commonplace. [2][3][4][5] These kinds of toxin treatments have high safety profiles and are very effective, but the risks of a variety of side effects or complications remain. [6][7][8][9][10][11][12][13][14] A physician who performs masseter toxin injections should be able to recognize different complications, along with their incidence rate, onset and time to recovery.…”
mentioning
confidence: 99%
“…The wet weight declined by 32% in the active site compared with the contralateral site, and was restored to 92% after six months. Ahn et al (2004) used Botox to treat benign masseter hypertrophy and observed that the masseter shrank the most in the first and second months after injection. The therapeutic effect lasted six months.…”
Section: Muscle Wet Weightmentioning
confidence: 99%